Modifiable factors for migraine prophylaxis: A mendelian randomization analysis - Zheng, Hui; Shi, Yun-Zhou; Liang, Jing-Tao; Lu, Liang-Liang; Chen, Min (Frontiers in Pharmacology, 2023)
Objective: To examine the causal effect of potentially modifiable risk factors contributing to migraine pathogenesis. Methods: We performed Mendelian randomization (MR) analyses and acquired data from UK Biobank, FinnGen Biobank, and the MRC IEU OpenGWAS data infrastructure. An inverse-variance weighted (IVW) model was used to examine the relationship between 51 potentially modifiable risk factors and migraine in 3215 participants with migraine without aura (MwoA), 3541 participants with migraine with aura (MwA), and 176,107 controls. We adopted a Bonferroni-corrected threshold of p=9.8×10-4 (0.05 divided by 51 exposures) as a sign of significant effect, and a p<0.05 was considered as the sign of a suggestive association. Results: More years of schooling significantly correlated with lower odds of MwoA pathogenesis (OR 0.57[95%CI 0.44 to 0.75], p<0.0001). More vitamin B12 intake (OR 0.49[95%CI 0.24 to 0.99], p =0.046) and lower level of stress (OR 8.17[95%CI 1.5 to 44.36], p=0.015) or anxiety disorder (OR 1.92×109[95%CI 8.76 to 4.23*1017], p=0.029) were suggestive to be correlated lower odds of MwoA pathogenesis. More coffee intake (OR 0.39[95%CI 0.22 to 0.7], p=0.001), lower level of eicosapentaenoic acid status (OR 2.54[95%CI 1.03 to 6.26], p=0.043), and more light physical activity (OR 0.09[95%CI 0.01 to 0.94], p=0.046) were suggestive to be associated with lower odds of MwA. Conclusions: The years of schooling, light physical activity, vitamin B12 intake, and coffee intake were the protective factors for migraine; stress, anxiety, and eicosapentaenoic acid status were harmful factors. Interventions could be developed based on modifying these factors for migraine prophylaxis.